Explicating the Culture of Historiographic Discourse. Does History Have the Subjunctive Mood? - N. I. Biryukov; N. F. Zheludova (Концепт: философия, религия, культура, 2023)
History has no subjunctive mood. This cliché has done a lot of harm to the science of history, even though it is usually voiced on its behalf and is presumed to express its basic methodological attitude. However, the maxim obviously disagrees with the practice of historiography as attested by numerous examples or, rather, counterexamples from classical texts, Greek as well as Roman, ancient Chinese as well as modern European, including Russian. Rejection of the subjunctive mood is usually due to the belief that conjectures can serve no positive function in the science of history and, therefore, have no right to appear in historical writings. However, if a serious scholar’s natural distaste for vain speculations turns into a virtual taboo on the study of historic opportunities, one is prone to ask whether this healthy scepticism about the trustworthiness of our cognitive procedures when applied to such fleeting matters as opportunities, possibilities and potentialities would not eventually lead to utter denial of the very existence of options and alternatives other than those actualised, i.e. to full-fledged fatalism. The matter is not that fatalism is unacceptable on both ontological and epistemological grounds, though it is. From the perspective of this paper the matter consists in that fatalism renders the historian’s craft meaningless. For to assert that there is but one reality is one thing, but to allege that this one reality is devoid of alternative opportunities is something dramatically different. It is impossible even to describe, least so understand, the course of events without reference to alternatives. He who ignores alternatives presents a distorted, oversimplified image of the past — an artificial, contrived construct that does not correspond to the past reality. A reality without alternatives is not a reality as it was, hence, any analysis, any explanation based on it or ensuing from it proves inadequate. Past was not devoid of alternative opportunities, and though these are not easy to study, they should not be left unstudied. And they are, indeed, not easy to study, because, unlike opportunities availed of, those unrealised are seldom properly portrayed in our sources. But who says that science is easy?